Clinical chorioamnionitis: where do we stand now? - Lukanović, David; Batkoska, Marija; Kavšek, Gorazd; Druškovič, Mirjam (Frontiers in Medicine, 2023)
Intraamniotic infection is an infection resulting in the inflammation of any combination of the amniotic fluid, placenta, fetus, fetal membranes, umbilical cord, or decidua. In the past, an infection of the amnion and chorion or both was dubbed chorioamnionitis. In 2015, an expert panel proposed replacing the term clinical chorioamnionitis with the term intrauterine inflammation or infection or both, abbreviated Triple I or simply IAI. However, the abbreviation IAI did not gain popularity, and this article uses the term chorioamnionitis. Chorioamnionitis is an infection that may occur before, during, or after labor. It can be acute, subacute, or chronic. In general, the clinical presentation of chorioamnionitis is defined as acute chorioamnionitis. The treatment of chorioamnionitis varies widely across the world due to different bacterial causes and the absence of sufficient evidence to support a specific treatment regimen. There are limited randomized controlled trials that have evaluated the superiority of antibiotic regimens for treating amniotic infections during labor. This lack of evidence-based treatment suggests that the current choice of antibiotics is based on limitations in existing research, rather than absolute science. Chorioamnionitis cannot be cured by antibiotic therapy alone without delivery, and therefore it is necessary to make a decision according to the guidelines for induction of labor or acceleration of delivery. When a diagnosis is suspected or established, it is therefore necessary to apply broad-spectrum antibiotics according to the protocol used by each country, and to continue with them until delivery. A commonly recommended first-line treatment for chorioamnionitis is a simple regimen consisting of amoxicillin or ampicillin and once-daily gentamicin. Although there are insufficient data to demonstrate the most appropriate antimicrobial regimen for the treatment of this obstetric condition, current available evidence indicates that women with clinical chorioamnionitis, mainly those with a gestational age ≥ 34 weeks and in labor, should be treated with this regime. However, antibiotic preferences may vary based on local policy, clinician experience and knowledge, bacterial causes of infection, patterns of antimicrobial resistance, maternal allergies, and drug availability.